2015
DOI: 10.3389/fped.2015.00092
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus bovis Bacteremia in Neonates in a Predominantly Hispanic Population

Abstract: BackgroundStreptococcus bovis bacteremia has been associated with gastrointestinal diseases, especially colon cancer, neoplastic colon polyps, and other malignancies of the GI tract in adults. Sporadic cases of S. bovis disease have also been reported in neonates and young infants. Although uncommon, S. bovis infection can cause fulminant neonatal sepsis and meningitis.ObjectivesWe report a series of pediatric patients with S. bovis bacteremia in a county hospital in a United States–Mexico border city in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In this study 21 (39.6%) died within the first year after their episode of bovis group streptococci bacteremia. There are not many studies to compare these data with but one study found a mortality rate among patients with bovis group streptococci bacteremia of 19% (Alvarez et al 2015). Similar to our study one third had colonoscopy and 19% were diagnosed with colorectal neoplasia.…”
Section: Discussionsupporting
confidence: 81%
“…In this study 21 (39.6%) died within the first year after their episode of bovis group streptococci bacteremia. There are not many studies to compare these data with but one study found a mortality rate among patients with bovis group streptococci bacteremia of 19% (Alvarez et al 2015). Similar to our study one third had colonoscopy and 19% were diagnosed with colorectal neoplasia.…”
Section: Discussionsupporting
confidence: 81%
“…Another study reported respiratory distress (100%) followed by abdominal distension (71.42%) and signs of pneumonia (28.57%) of neonatal sepsis [11]. Unusual presentation of generalised neonatal seizures was seen in a study [12].…”
Section: Fig 2: Treatment Outcome Of Neonatal Septicemia Discussionmentioning
confidence: 91%
“…Streptococcus bovis is a Gram-positive, Lancefield group D Streptococcus which is found in the pharynx, nose, and gastrointestinal tract of healthy humans [ 3 ]. It is an unusual etiology of human diseases; however, it is known to cause infective endocarditis in hosts with predisposing cardiac defects [ 4 ].…”
Section: Discussionmentioning
confidence: 99%